Densidade de estocagem de lambari (Astyanax altiparanae) em tanques-rede - Costa, Beatriz Braun (2011)
With the increased interest in growing native fish species the tetra has been highlighted nationally in the marketing of fish facing the two niche markets: as a snack in bars and restaurants and other natural bait for sport fishing. Therefore, studies on the stocking density are needed for better understanding in response to performance than can affect the growth, nutrition and animal behavior. This study aimed to evaluate the economic viability and growth performance of the tetra (Astyanax altiparanae) in cages, subjected to different stocking rates. The experiment was conducted on the premises of the UPD Pirassununga, APTA Pole Central East, in cages of 1m3, villages in densities: 250,450 and 600 fish per tank with 4 repetitions. The temperature, water clarity, dissolved oxygen an pH were daily measured. The tetra were fed extruded commercial diet containing 36%of protein. The experiment lasted 57 days and monthly samples were collected to evaluate the development and adjust amount of feed. To verify the significance between treatment means was used Tukey s test at 5% probability. The results showed increasing linear effect for variable total biomass (p<0,05) as opposed to the linear effect (p<0,05) for average consumption of feed as well as weight gain, average final length and final weight medium according to the increase of stocking density. The physic-chemical parameters remained at adequate levels. It is concluded that stocking density affects the development of juveniles of tetra and the density of persons over fishes/m³. Can still be used in the cultivation of 600 fishes/m³ tetra juveniles in cages, resulting in higher total biomass, although they result in smaller populations.